2015
DOI: 10.1007/s11241-015-9245-9
|View full text |Cite
|
Sign up to set email alerts
|

A pre-order relation for exact schedulability test of sporadic tasks on multiprocessor Global Fixed-Priority scheduling

Abstract: International audienceIn this paper we present an exact schedulability test for sporadic real-time tasks scheduled by the Global Fixed Priority (G-FP) Fully Preemp-tive Scheduler on a multiprocessor system. The analysis consists in mod-eling the system as a Linear Hybrid Automaton (LHA), and in performing a reachability analysis for states representing deadline miss conditions. To mitigate the problem of state space explosion, we propose a pre-order relationship over the symbolic states of the model: states th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Consider, for example, global and partitioned multiprocessor scheduling. Some exact schedulability tests for global static-priority [63], [65] and global EDF [12], [19], [39] scheduling are known, but their scalability is such that they cannot be applied to anything more than toy examples (from an industrial perspective). When sufficient schedulability tests are used, the current state-of-the-art analyses for global scheduling, both for static-priority [31], [40], [41], [63] and EDF [11], [13], [64], stem from the seminal work by Baker [10], which leads to an interference upper bound with a multiplicative factor of 1/m in the resulting tests, where m is the number of processors.…”
Section: Generalization In Implementation Spacementioning
confidence: 99%
“…Consider, for example, global and partitioned multiprocessor scheduling. Some exact schedulability tests for global static-priority [63], [65] and global EDF [12], [19], [39] scheduling are known, but their scalability is such that they cannot be applied to anything more than toy examples (from an industrial perspective). When sufficient schedulability tests are used, the current state-of-the-art analyses for global scheduling, both for static-priority [31], [40], [41], [63] and EDF [11], [13], [64], stem from the seminal work by Baker [10], which leads to an interference upper bound with a multiplicative factor of 1/m in the resulting tests, where m is the number of processors.…”
Section: Generalization In Implementation Spacementioning
confidence: 99%
“…They adopt a dynamic server algorithm, separating each server from the rest of the system, and thereby enabling component-based scheduling analysis. This method is subsequently applied to a multicore global scheduling system and extended with a weak simulation in [25] to reduce the state space of complex models. The approaches of [26,27] use TA to describe a hierarchical scheduling system, while both of them are limited to periodic tasks isolated from each other.…”
Section: Related Work and Contributionsmentioning
confidence: 99%
“…the state-of-the-art) and exact test for G-FP by relying on accurate statespace pruning. Sun and Lipari [44,45] proposed an exact analysis for G-FP by modeling the system as a linear hybrid automaton. The authors identified a pre-order relationship over the symbolic states of the model to mitigate the problem of state space explosion.…”
Section: Related Workmentioning
confidence: 99%
“…Also, their corresponding schedulability problems have been proven to be PSPACE-complete by Geeraerts et al [27]. To date, all the techniques that allow implementing exact schedulability tests for G-FP [44,45] and G-EDF [3,27,14] suffer from severe scalability issues, and many of them can produce a result in a reasonable amount of time only when the task parameters belong to fairly limited ranges (e.g., see the experimental results in [17]).…”
Section: Introductionmentioning
confidence: 99%